K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 6 2017

\(\left(5-2x\right)\left(2x+7\right)=4x^2-25\)\(\Leftrightarrow\left(5-2x\right)\left(2x+7\right)=\left(2x+5\right)\left(2x-5\right)\)

\(\Leftrightarrow-\left(2x-5\right).\left(2x+7\right)-\left(2x+5\right)\left(2x-5\right)=0\)

\(\Leftrightarrow\left(2x-5\right)\left(-7-2x-2x-5\right)=0\)

\(\Leftrightarrow\left(2x-5\right)\left(-12-4x\right)=0\)\(\Leftrightarrow\orbr{\begin{cases}2x-5=0\\-12-4x=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{5}{2}\\x=-3\end{cases}}\)

Vậy x=5/2 hoặc x=-3

24 tháng 7 2016

a) 4x^2 - 25 - ( 2x - 5) .( 2x + 7) = 0

<=>4x2-25-(4x2+14x-10x-35)=0

<=>4x2-25-4x2-14x+10x+35= 0 

<=>-4x+10= 0 

<=>x= 5/2

b)  x^3 + 27 + ( x+3). ( x -9) = 0

<=>x3+33+(x+3)(x-9)=0

<=>(x+3)(x2-3x+9)+(x+3)(x-9)=0

<=>(x+3)(x2-3x+9+x-9) =0

<=>(x+3)(x2-2x)=0

<=>(x+3)(x-2)x= 0

<=>x=-3 hoặc x=2 hoặc x=2

19 tháng 10 2019

4x2 - 25 - (2x - 5)(2x + 7) = 0

<=> (2x)2 - 52 - (2x - 5)(2x + 7) = 0

<=> (2x - 5)(2x + 5) - (2x - 5)(2x + 7) = 0

<=> (2x - 5)(2x + 5 - 2x - 7) = 0

<=> (2x - 5) . (-2) = 0

<=> 2x - 5 = 0

<=> 2x = 5

<=> x = 5/2

19 tháng 11 2018

\(\left(5-2x\right)\left(2x-7\right)=4x^2-25\)

\(-\left(2x-5\right)\left(2x-7\right)=\left(2x\right)^2-5^2\)

\(\left(2x-5\right)\left(7-2x\right)=\left(2x-5\right)\left(2x+5\right)\)

\(\left(2x-5\right)\left(7-2x\right)-\left(2x-5\right)\left(2x+5\right)=0\)

\(\left(2x-5\right)\left(7-2x-2x-5\right)=0\)

\(\left(2x-5\right)\left(2-4x\right)=0\)

\(\Rightarrow\orbr{\begin{cases}2x-5=0\\2-4x=0\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}x=\frac{5}{2}\\x=\frac{1}{2}\end{cases}}\)

23 tháng 10 2016

-_- bài này hôm qua lm rùi

5 tháng 8 2016

1) \(4x^2-25-\left(2x-5\right)\left(2x+7\right)=0\)

\(\Leftrightarrow\left(2x-5\right)\left(2x+5\right)-\left(2x-5\right)\left(2x+7\right)=0\)

\(\Leftrightarrow\left(2x-5\right)\left(2x+5-2x-7\right)=0\)

\(\Leftrightarrow\left(2x-5\right).-2=0\)

\(\Leftrightarrow-4x+10=0\)

\(\Leftrightarrow-4x=-10\)

\(\Leftrightarrow x=\frac{5}{2}.\)

Vậy \(S=\left\{\frac{5}{2}\right\}\)

2)\(x^3+27+\left(x+3\right)\left(x-9\right)=0\)

\(\Leftrightarrow\left(x+3\right)\left(x^2-3x+9\right)+\left(x+3\right)\left(x-9\right)=0\)

\(\Leftrightarrow\left(x+3\right).\left(x^2-3x+9+x-9\right)=0\)

\(\Leftrightarrow\left(x+3\right)\left(x^2-2x\right)=0\)

\(\Leftrightarrow\left(x+3\right).x.\left(x-2\right)=0\)

\(\Leftrightarrow x+3=0\)hoặc \(x=0\)hoặc \(x-2=0\)

\(\Leftrightarrow x=-3\)hoặc \(x=0\)hoặc \(x=2\)

Vậy \(S=\left\{-3;0;2\right\}\)

21 tháng 10 2016

8x2+30x+7=0

 8x2+16x+14x+7=0

8x(x+2) +7(x+2)=0

(8x+7)(x+2)=0

=>\(\orbr{\begin{cases}8x+7=0\\x+2=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-\frac{7}{8}\\x=-2\end{cases}}}\)

21 tháng 10 2016

a)

4x2-8x+4=2(1-x)(x+1)

4x2-8x+4-2+2x2=0

6x2-8x+2=0

2(3x2-4x+1)=0

3x2-3x-x+1=0

3x(x-1) -(x-1)=0

(3x-1)(x-1)=0

\(\Rightarrow\orbr{\begin{cases}3x-1=0\\x-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=1\end{cases}}}\)

16 tháng 8 2017

\(4x^2-25-\left(2x-5\right)\left(2x+7\right)=0\)

\(\Leftrightarrow\left(2x+5\right)\left(2x-5\right)-\left(2x-5\right)\left(2x+7\right)=0\)

\(\Leftrightarrow\left(2x-5\right)\left(2x+5-2x-7\right)=0\)

\(\Leftrightarrow-2\left(2x-5\right)=0\)

\(\Leftrightarrow2x-5=0\)

\(\Leftrightarrow x=\frac{5}{2}\)

28 tháng 10 2018

Ta có:

\(a)\left(2x-5\right)\left(x+2\right)-2x\left(x-1\right)=15\)

\(\Leftrightarrow\left(2x^2-x-10\right)-\left(2x^2-2x\right)=15\Leftrightarrow x-10=15\)

\(\Leftrightarrow x=25\)

\(b)\left(5-2x\right)\left(2x+7\right)=4x^2-25\)

\(\Leftrightarrow\left(5-2x\right)\left(2x+7\right)=\left(2x-5\right)\left(2x+5\right)\)

\(\Leftrightarrow\left(5-2x\right)\left(4x+12\right)=0\)

\(5-2x=0\Leftrightarrow x=\frac{5}{2}\)

\(4x+12=0\Leftrightarrow x=-3\)

Vậy ..........................................